The Effect of Mind Mapping Strategy Towards Students Writing Skill at the Tenth Grade Students of MA Anwarul Hidayah Ciputri Menes Pandeglang in Academic Year 2022/2023 - Elawati, Elawati; Riandi, Riandi; Gumelar, Rizdki Elang (Journal of English Education Studies, 2022)
This study aims to investigate the implementation of Mind Mapping strategy towards student's writing descriptive at the tenth-grade students of MA Anwarul Hidayah Menes Pandeglang. The study used quantitative approach, while the method used is quasi experimental method with pre-test and post-test design. It used a triangulation of data collection methods involving pre-test, treatment and post-test. The data obtained from 2 classes, they are experiment and control class. The experimental class for this research was XA and the control class was XB. Each class consists of 30 students. The total sample is 60 students. The experimental class’s mean score on the pre-test was 50.23, while the control class’s mean score on the pre-test was 48.57. On the other hand, the post-test result is, the mean score of experimental class was 69.07, while the mean score of control class was 63.33. The hypothesis calculating was done by using SPSS 22. The result obtained from hypothesis test is 0.00 < 0.05 it means that there is significant effect of Mind Mapping strategy towards student's writing descriptive at the tenth-grade students of MA Anwarul Hidayah Ciputri Menes Pandeglang in academic year 2022/2023.